Genetic Basis of Biofilm Formation Genes Ebp and Bph (phos) among Multidrug Resistance Enterococcus faecalis Isolates, Iraq - Muna Salman Attia; Ibtisam Habeeb Al-Azawi (Medical Journal of Babylon)
Background:Biofilm produced by Enterococcus spp. increase their inherent and acquired antibiotic resistance, posing a significant challenge to infection treatment, particularly in virulent strains. Objective:This study aimed to investigate some genes responsible for biofilm formation (Bph (phos) and EbpB) by polymerase chain reaction (PCR) technique. Materials and Methods:A total of 130 clinical samples were collected during this study, which were obtained from patients who were admitted to Feminine and Children Teaching Hospital in Al-Diwaniyah City during a period extending from (November 2022 to March 2023). All samples were subjected to culturing on different media (blood agar, MacConkey, Bile Esculin agar, and M-El chromogenic ager), after which catalase and oxidase tests were conducted biochemically. After cultivation, the VITEK-2 compact system was used to identify the samples. The isolates were investigated genotypically for harboring biofilm formation genes, including EbpB and Bph (phos), by molecular method (PCR). Results:The VITEK-2 compact system revealed that only 12 isolates were identified as E. faecalis. The most effective antibiotics against E. faecalis were (vancomycin, teicoplanin, linezolide, tigecycline, and ampicillin), and the highest resistance was against erythromycin (100%) and tetracycline (91.6%). Enterococcus faecalis isolates were investigated genotypically for harboring biofilm formation genes that include EbpB and Bph (phos) by molecular methods, PCR. The results showed that EbpB and Bph (phos) genes were positive for all isolates with a percentage of 100%. Conclusions:It was found that the presence of biofilm formation genes in E. faecalis EbpB, and phos (Bph) increase the pathogenicity of this pathogen. These genes showed a high percentage among E. faecalis isolates. Also, all isolates had the potential to form a biofilm, which complicates their treatment with antibiotics, confirming the critical need to develop novel antimicrobial agents that control the infection associated with the development.